1D/3D Alloying Induced Phase Transition in Light Absorbers for Highly Efficient Sb2Se3 Solar Cells. Issue 4 (25th February 2020) - Guo, Chunsheng; Liang, Xiaoyang; Liu, Tao; Liu, Yufan; Yang, Lin; Lai, Weidong; Schropp, Ruud E. I.; Song, Dengyuan; Mai, Yaohua; Li, Zhiqiang
Abstract : A simple binary inorganic antimony selenide (Sb2 Se3 ) compound is attractive as a promising light absorber for low‐cost and high‐efficiency photovoltaics. The external quantum efficiencies of Sb2 Se3 solar cells are now approaching the optical limit values, which are comparable with the traditional well‐developed solar cells (such as Si, CuInGaSe2, CdTe, etc). However, the power conversion efficiency of the Sb2 Se3 devices is constrained by the open‐circuit voltage ( V OC ) deficit, due to the intrinsic high resistivity and low element‐doping efficiency in such one‐dimensional (1D) crystals. Herein, a highly conductive, three‐dimensional (3D) crystal‐structure AgSbSe2 phase, formed by phase transition from low symmetry binary Sb2 Se3, is introduced to control the doping density in the alloyed (Sb2 Se3 ) x (AgSbSe2 )1− x films utilizing configurational entropy. Guided by this alloying concept, 1D–3D (Sb2 Se3 ) x (AgSbSe2 )1− x alloy films with tunable doping densities are obtained. As a consequence, a noticeable improvement in V OC by >18% is observed in solar cells based on the (Sb2 Se3 ) x (AgSbSe2 )1− x alloy absorber layer, compared with the reference cell with a pure Sb2 Se3 absorber, leading to a high conversion efficiency of 7.8%. This alloying model provides a universal approach to control the photoelectrical properties for high‐efficiency Sb2 Se3 ‐based solar cells. Abstract : Sb2 Se3 /AgSbSe2 alloying thin films are fabricated by using a close spaced sublimation technique. The doping density of the (Sb2 Se3 ) x (AgSbSe2 )1− x alloy is about one order of magnitude higher than that of pure Sb2 Se3 films. The alloying approach boosts the solar cell open‐circuit voltage (V OC ) from lower than 400–475 mV, and the V OC further increases up to more than 500 mV after 1100‐h illumination.